Foundations of the South African Heart Association: The South African Society of Cardiac Practitioners 1985 - 1999 - Dalby, Anthony J. (SA Heart Journal, 2018)
The South African Heart Association (SA Heart®) was established in 1999. Prior to 1999, 2 professional societies represented the interests of cardiologists and cardiac surgeons in South Africa – the South African Cardiac Society and the South African Society of Cardiac Practitioners. The latter was formed in 1985 by cardiologists in private practice to serve the interests of private practitioners. At the time, the South African Cardiac Society was based mainly in the academic training institutions and the need arose to have a representative body addressing the needs of private practice. In the late 1990s it became clear that the 2 societies were competing for the same support from industry and were diluting each other’s influence. The realisation that strength lay in unity led to an amalgamation of the 2 societies in 1999 – to form the SA Heart® Association. In this commentary, Dr Tony Dalby provides us with a personal reflection of the history of the South African Society of Cardiac Practitioners. In future issues of the SA Heart® Journal, we will feature similar personal reflections to document the history of the South African Cardiac Society and the South African Heart Association.